Exploring the nature and meaning of participation in the Tsitsa River Catchment - Ralekhetla, Mateboho Mary (Rhodes University, 2026)
This thesis investigates the nature and meaning of participation to the different stakeholders in the Tsitsa Project in the Tsitsa River catchment, focusing on its implications for epistemic justice and sustainable natural resource management. Participation is increasingly recognised as a cornerstone of sustainable resource management, yet its implementation often marginalises certain forms of knowledge, reinforcing existing power dynamics and undermining sustainability. Drawing on participatory governance theories and the concept of epistemic justice, this study aims to explore some of the power dynamics in the context of the Tsitsa Project (TP) and to advance both the conceptual understanding and practice of participation, and participatory governance. The research is grounded in critical realism, a philosophical lens that aligns with the theory of complex social-ecological systems, enabling a deeper exploration of underlying structures and power dynamics. A narrative inquiry approach was employed to collect data, capturing the lived experiences and stories of community members, researchers, implementers, and government officials who participated in Tsitsa Project activities. To present the findings, poetic inquiry was utilized, offering a creative and reflective medium to convey the nuanced, affective dimensions of participation. The findings reveal a tension between the hopes and frustrations that participants experience when entering the participatory space. Issues of tokenistic inclusion were also described, which were a source of dissatisfactory participatory experiences for those who experienced them, and thereby risked the promotion of an instrumental approach to participation as opposed to an emancipatory approach as intended. The exclusion of others in the form of tokenistic inclusion not only undermines inclusive decision-making but also perpetuates historical injustices—including epistemic injustice. The thesis argues for a reimagining of participation that centres on recognising and legitimising diverse epistemologies. By fostering equitable knowledge-sharing platforms, participatory processes can contribute to more just and sustainable outcomes. This work advances the understanding of participation as a vehicle for epistemic justice and provides practical recommendations for inclusive governance in the Tsitsa catchment and beyond.
question of epistemic (in)justice?
Keywords: Uncatalogued